Sustainable Solutions to ‘Complex Problem-Solving’ A Key to Effective Community and Industry Engagement and Partnerships by University Researchers - Cameron Richards; Neil Tanquilu (Department of Urban and Regional Planning, Universitas Diponegoro, 2014)
Community and industry engagement by universities and academics are sometimes prone to accusations of exclusive or academic ‘talk-fests’ which can reinforce rather than resolve the ‘bridgeable disconnect’ between the general community and particular organizations with vested interests (Grayson, 2010). Concrete modes and strategies of ‘linking knowledge to action’ are needed to build upon the participatory exchange or mediation of stakeholder perspectives and interests. This paper reports on the exploration, development and application of the kind of convergent and also interdisciplinary approach to development studies which might: (a) better link theory and practice as a basis for the elusive goal of strategic ‘sustainability’, and (b) also encourage and optimize authentic, collaborative, and complex modes of problem-solving as a key to community and industry engagement by academic institutions and researchers. It will do so in relation to some practical case studies in such partnerships.